Studies in maritime history - Mathew, Kuzhippalli Skaria, 1939-; Pondicherry University (Pondicherry : Pondicherry University, 1990)
History of navigation in Indian Ocean, during the period 16th-18th century; contributed research papers
Includes bibliographical references and index
Keywords: Merchant marine -- India -- History; Indian Ocean Region -- Commerce -- History; India -- Commerce -- History